Analisis Tingkat Efisiensi Paket Teknologi Usahatani Padi Gogo di Lahan Tadah Hujan - Teguh Prasetyo; Cahyati Setiani (Universitas Muhammadiyah Purworejo, 2018)
Upland rice farming carried out on rainfed land is classified as high risk, so the development of upland rice in rainfed land is relatively slow. This is because the farming that is currently being implemented is considered inefficient. In this regard, a study related to the level of efficiency of upland rice farming technology packages is needed with the aim of knowing the productivity and feasibility of upland rice farming in rainfed land. The technology packages introduced were the new high yielding varieties (VUB) Inpago 5, Inpago 8, Inpago 9, and Inpari 19. The planting system was carried out in a row of legowo with a dosage of urea fertilizer of 125 kg/ha and Phonska of 275 kg / ha. The use of organic fertilizers is fulfilled from the collection of faeces and leftover cattle feed maintained by cooperator farmers, which is between 2-3 tons. The data collected included the yield of harvested dry unhulled rice and milled dry grain. To assess the feasibility of each technology package, an R / C analysis is used, namely the ratio between revenues and total costs incurred during the production process. To determine the level of efficiency of the studied technology package, it is measured from the percentage of production costs to the total cost of farming patterns of farmers. The results of the study showed that milled dry unhulled rice (GKG) showed that the Inpago 8 variety upland rice had the highest yield, namely 5.52 t / ha compared to the other 3 variates, namely between 4.8-5.3 t / ha GKG. From the results of financial calculations on rice farming, it can be seen that the R / C obtained in farmer pattern farming is lower than the introduced farming technology package with VUB Inpago 5 and Inpago 8. The technology package with VUB Inpago 5 and Inpago 8 can be said to be more efficient because the efficiency value exceeds the estimated 100%, respectively 114.60% and 120.67%, while the technology package using Inpago 9 and Inpari 19 varieties is less efficient when compared to the farmer pattern. Inpago 8 rice variety is the variety with the highest productivity and efficiency level when compared to other varieties. With an increase in the productivity and profitability of Inpago 8 rice farming, it has the opportunity to be developed in rainfed land widely. Keywords: Efficiency, varieties, upland rice, rainfed